2019
DOI: 10.1039/c9ra08660a
|View full text |Cite
|
Sign up to set email alerts
|

Removal of anthracene in water by MIL-88(Fe), NH2-MIL-88(Fe), and mixed-MIL-88(Fe) metal–organic frameworks

Abstract: Three adsorbents based on the metal–organic frameworks (MOFs), viz.; MIL-88(Fe), NH2-MIL-88(Fe), and mixed-MIL-88(Fe) were synthesized using a microwave-assisted solvothermal technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 54 publications
10
27
0
Order By: Relevance
“…Figure 2a exhibits the XRD patterns of as-synthesized MIL-88B-Fe and simulated MIL-88B-Fe. The diffraction peaks are indeed matched with that of the reported MIL-88B-Fe structure [26], confirming the successful preparation of MIL-88B-Fe MOF. The molecular structure of MIL-88B-Fe is further investigated by FTIR spectrum, and the relevant result is presented in Fig.…”
Section: Characterization Of Mil-88b-fe Mofsupporting
confidence: 78%
“…Figure 2a exhibits the XRD patterns of as-synthesized MIL-88B-Fe and simulated MIL-88B-Fe. The diffraction peaks are indeed matched with that of the reported MIL-88B-Fe structure [26], confirming the successful preparation of MIL-88B-Fe MOF. The molecular structure of MIL-88B-Fe is further investigated by FTIR spectrum, and the relevant result is presented in Fig.…”
Section: Characterization Of Mil-88b-fe Mofsupporting
confidence: 78%
“…The Langmuir, Freundlich and Temkin isotherms were used to describe the adsorption of MCPA onto MIL-101(Cr). The models are described by the following equations [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Chen et al [ 58 ] UiO-66 showed significantly higher adsorption capacity of tetracycline hydrochloride (TH; 23.1 mg/g) antibiotics compared to the adsorption capacity of AC for the same substance (1.98 mg/g) previously reported [ 59 ]. In a report by Zango et al [ 60 ] MIL-88(Fe) showed an adsorption capacity of 23.6 mg/g for adsorption of highly toxic PAH anthracene (ANT), performing better than AC with an adsorption capacity of 8.35 mg/g in a previous report [ 61 ]. Several other reports of MOF application as adsorbents of wastewater emerging pollutant and their adsorptive performance are listed in Table 1 .…”
Section: Specific Improvement Strategies Related To Each Role Of Metal-organic Framework In Wastewater Treatmentmentioning
confidence: 99%